Platelet microparticles level in juvenile idiopathic arthritis: A pediatric population-based cross-sectional study in a tertiary care center - Naresh Kumar; K Anu Punnen; Sukesh Chandran Nair; Visalakshi Jayaseelan; T Sathish Kumar (Indian Journal of Rheumatology)
Background: Platelet-derived microparticles (PMPs) are small vesicles that are released from the plasma membrane upon platelet activation, which are then involved in haemostasis, vascular health, and have recently been shown to be intimately involved in immune responses. Aims and Objectives: We aimed to evaluate the level of plasma Platelet-derived micro particles in children with JIA and to assess the relationship between PMP levels and disease activity in JIA. Materials and Methods: Children with JIA who fulfilled the International League of Associations for Rheumatology (ILAR) classification criteria for juvenile idiopathic arthritis were included. They were categorised into active disease group and inactive disease as assessed by Wallace criteria. Samples were run in Navios flow cytometer (Beckman Coulter). Platelet microparticles were identified by MPs positive for both Annexin V and CD41 antibodies. Results: Out of 26 children with JIA, 12 had active disease group and 14 had inactive disease as assessed by Wallace criteria. Mean PMP level was 83507 cells/μl and 34904 cells/μl in active and inactive disease respectively (P = 0.06). There was no significant correlation between PMP and CRP levels (P = 0.75 and r = 0 .102) or PMP and ESR levels (P = 0.56 and r = -0.186) in JIA children with active disease. Conclusion: PMP levels were significantly elevated in disease activity of JIA and could represent a new biomarker reflecting the state of cell activation in JIA. PMP role in the inflammatory processes needs to be further elucidated.